Ethnomatematics Based Learning Video Media on Mathematical Content - Juliantini, Ni Komang Indah; Alexander Hamonangan Simamora; I Gde Wawan Sudatha (MIMBAR PGSD Undiksha, 2023)
The lack of innovative learning media during learning and the lack of instilling concepts in mathematics causes learning to be less meaningful. This development research aims to determine the design, feasibility, and effectiveness of Ethnomatematics-based Mathematics Learning Videos on speed material for fifth-grade elementary school students. This research belongs to the type of development research that was developed using the ADDIE model. The subjects of this research trial were learning content (material) experts, instructional design experts, instructional media experts, and 24 fifth-grade elementary school students. Data collection in the study was carried out using the questionnaire method and the test method. Data analysis techniques using qualitative data analysis techniques, quantitative descriptive data analysis, and inferential statistics (t-test). The results showed that the assessment of learning media experts obtained a percentage of 94.79% with very good qualifications, the results of the assessment of learning design experts obtained a percentage of 95.83% with very good qualifications, the results of the assessment of material experts obtained a percentage of 97.41% with qualifications very good, the results of student assessments through individual trials obtained a percentage of 97.22% with very good qualifications, the results of student assessments through small groups obtained a percentage of 98.29% with very good qualifications. It was concluded that the ethnomathematics-based instructional video media on the mathematics content of speed material for fifth-grade elementary school students could help students improve their understanding of learning concepts, especially in mathematics, to improve student learning outcomes.